Transformasi Pesan Dakwah dan Mobilitas Sosial - Saleh, Duden Aiman; Sofyan, Karyana (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This research aims to analyze the dynamics of da'wah message transformation and its impact on social mobilization, as well as identify factors that influence the success of Bandung Regency's social mobilization. This research uses a qualitative approach with phenomenological methods. The theory used is Max Weber's social action theory. The results revealed that through message transformation, da'wah can reach a wider audience, using various media and approaches that are in accordance with the current conditions of society. Social mobilization triggered by da'wah can strengthen solidarity between community members. By creating a strong social network, da'wah is able to connect various elements of society, so that collaboration in overcoming social problems becomes more effective. The determining factors in the success of social mobilization consist of social processes, social interactions, social mobility, and social dynamics.